1971
DOI: 10.1111/j.1600-0722.1971.tb02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in inflamed human dental pulp

Abstract: Dental pulps from 45 caries-free primary or permanent teeth and from 24 carious primary teeth were investigated for presence of mast cells (MC) . All the pulps were removed from split teeth and fixed in Newcomer's fluid or lead acetate-formalin. Serial sections stained with hematoxylin-eosin, astra blue (pH 0.2-0.3) + nuclear fast red, and toluidine blue (pH 1.0) demonstrated that pulps without inflammatory cells or with a few small lymphocytes were devoid of typical MC, even in the strongly metachromatic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…The stimuli delivered to the sensitive areas by the test food appeared to be mechanical and thermal rather than chemical (gustatory), as we used a tasteless and odourless thickening agent as the test food material (see ‘’). The major finding of this study (i.e., lying down induces a decrease in Duration 1st SH ) is consistent with a previous study using saliva as the test material (4), but not with studies using small amounts (<10 mL) of barium (3, 7) in which body posture was found not to alter the duration of oral swallowing. Differences in the materials (thickening agent, saliva, and barium) are most likely the cause, at least in part, of the contradictions between the present and previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The stimuli delivered to the sensitive areas by the test food appeared to be mechanical and thermal rather than chemical (gustatory), as we used a tasteless and odourless thickening agent as the test food material (see ‘’). The major finding of this study (i.e., lying down induces a decrease in Duration 1st SH ) is consistent with a previous study using saliva as the test material (4), but not with studies using small amounts (<10 mL) of barium (3, 7) in which body posture was found not to alter the duration of oral swallowing. Differences in the materials (thickening agent, saliva, and barium) are most likely the cause, at least in part, of the contradictions between the present and previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…The authors then examined the pressure changes in the upright and supine positions in a large number of normal subjects ( n = 1219) and showed that the oral phase of swallowing did not differ between the two positions when a small (spoonful) amount of barium was given, but was prolonged in the supine position when larger amounts (10–30 mL) of barium and water were given (3). A later study analysed electromyogram (EMG) activities of the lateral pterygoid and digastric muscles during swallowing of saliva and documented that these muscles started firing earlier (30–100 ms) in the 45° inclined and supine positions than in the upright position, suggesting that the supine posture shortens the oral phase of swallowing (4). In contrast, a recent analysis of EMG patterns of the suprahyoid (SH) muscles recorded during swallowing of 5 mL of water revealed that the SH EMG in the inclined position (60° reclining from vertical with 60° chin‐tuck) was longer than in the upright and inclined (30° reclining from vertical with 30° chin‐tuck) positions, suggesting that inclining body posture to 60° prolongs the oral phase of swallowing (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies using surface EMG performed group‐average analysis for the duration and amplitude of muscle activity with regard to the different body angulations during deglutition (4–11). No statistical significance was observed in these studies between the parameters even with a large number of subjects because of large variations among individuals (6–11), as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown that the order of onset and duration of activity in the various mandibular elevator and depressor muscles depends to some extent on the posture of the subject. 10 Despite some variation in the order of onset of activity, the mandibular elevator and depressor muscles show almost simultaneous activity in swallowing.9 Mean durations of activity found by Moller in swallowing saliva (after amalgamation of results from the two sides) were anterior temporal muscle, 1,042 milliseconds (msec); posterior temporal muscle, 1,041 msec; masseter muscle, 970 msec; medial pterygoid muscle, 1,083 msec; anterior digastric muscle, 1,188 msec; mylohyoid muscle, 1,139 msec; and lateral pterygoid muscle, 1,133 msec. The mean durations of anterior digastric muscle activity of about 1.0 sec for a swallow of saliva in the present series are, therefore, reasonably consistent with Moller's results.…”
Section: Methodsmentioning
confidence: 97%